Istranca Dağları' ndan (Trakya Bölgesi) iki yeni birlik: Carpino betuli-Fagetum orientalis Yarcı Ass. Nov. ve Querco cerridis-Carpinetum orientalis Yarcı Ass. Nov. - (:unkn) unknown (My University, 2002)
Bu makale, Trakya'nın kuzeyinde uzanan Istranca (Yıldız) Dağlan'nm vejetasyonu üzerinde bir çalışmayı sunmaktadır. Araştırılan bölgenin vejetasyonu, sintaksonomik olarak, iki birlikten meydana gelir. Bu birlikler; Carpino betuli-Fagetum orientalis Yarcı ve Querco cerridis-Carpinetum orientalis Yarcı'dır. Çalışma, klasik Braun-Blanquet metoduna göre yapılmıştır. Birlikler, Fitososyolojik Adlandırma Kodu'na göre adlandırılmış olup, Querco-Fagea Quezel et al., 1980 üst sınıfı, Quercetea pubescentis Quezel et al., 1978 sınıfının Quercetalia pubescentis Doing Kraft, 1955 takımına dahil edilmektedir. Her iki birlik de ilk defa rapor edilmektedir.

This article presents a study on the vegetation of Istranca (Yıldız) Mountains lying in the northern Thrace. Syntaxonomically, the vegetation of the study area consists of two associations. These associations are; Carpino betuli-Fagetum orientalis Yarcı and Querco cerridis-Carpinetum orientalis Yarcı. The study was realized by using classic Braun- Blanquet method. Associations were named according to phytosociological nomenclature code and'are included in Quercetalia pubescentis Doing Kraft, 1955 order; Querco-Fagea Quezel et al., 1980 superclass, Quercetea pubescentis Quezel et al., 1978 class. Both these associations are reported for the first time.
Two new associations from the Istranca Mountains (Thrace Region): Carpino betuli-Fagetum orientalis Yarcı Ass. Nov. and Querco cerridis-Carpinetum orientalis Yarcı Ass. Nov.